A risk-based method for planning of bus–subway corridor evacuation under hybrid uncertainties. (July 2015) - Lv, Y.; Yan, X.D.; Sun, W.; Gao, Z.Y.
Abstract: Emergencies involved in a bus–subway corridor system are associated with many processes and factors with social and economic implications. These processes and factors and their interactions are related to a variety of uncertainties. In this study, an interval chance-constrained integer programming (EICI) method is developed in response to such challenges for bus–subway corridor based evacuation planning. The method couples a chance-constrained programming with an interval integer programming model framework. It can thus deal with interval uncertainties that cannot be quantified with specified probability distribution functions. Meanwhile, it can also reflect stochastic features of traffic flow capacity, and thereby help examine the related violation risk of constraint. The EICI method is applied to a subway incident based evacuation case study. It is solved through an interactive algorithm that does not lead to more complicated intermediate submodels and has a relatively low computational requirement. A number of decision alternatives could be directly generated based on results from the EICI method. It is indicated that the solutions cannot only help decision makers identify desired population evacuation and vehicle dispatch schemes under hybrid uncertainties, but also provide bases for in-depth analyses of tradeoffs among evacuation plans, total evacuation time, and constraint-violation risks. Highlights: An inexact model is developed for the bus–subway corridor evacuation management. It tackles stochastic and interval uncertainties in an integer programming problem. It can examine violation risk of the roadway flow capacity related constraint. It will help identify evacuation schemes under hybrid uncertainties.